2021
DOI: 10.1101/2021.01.14.21249808
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

U-shaped effect of blood pressure on structural OCT metrics and retinal blood flow autoregulation in ophthalmologically healthy subjects

Abstract: Objective1) To investigate the effect of low blood pressure (BP), treated arterial hypertension (AHT), and untreated AHT on the ganglion cell-inner plexiform layer (GCIPL) and the retinal nerve fiber layer (RNFL) thickness of non-glaucomatous eyes and 2) to elucidate whether this effect is related to crossing the lower limit of retinal blood flow (RBF) autoregulation.DesignCross-sectional, case-control.SubjectsWe included 96 eyes of 96 ophthalmologically healthy subjects (age 50-65). Participants were prospect… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…An inverse U-shaped effect exists between BP status and structural OCT metrics, with both low and high BP associated with inner retinal layer thinning. 48 ACEIs and diuretics have been proposed to have differential effects on the ocular microvasculature structurally and functionally in terms of diurnal BP regulation compared to other classes of antihypertensive medications. 47 Moreover, only a small autoregulatory reserve is present in individuals with low BP, or in those with intensively treated arterial hypertension.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An inverse U-shaped effect exists between BP status and structural OCT metrics, with both low and high BP associated with inner retinal layer thinning. 48 ACEIs and diuretics have been proposed to have differential effects on the ocular microvasculature structurally and functionally in terms of diurnal BP regulation compared to other classes of antihypertensive medications. 47 Moreover, only a small autoregulatory reserve is present in individuals with low BP, or in those with intensively treated arterial hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…47 Moreover, only a small autoregulatory reserve is present in individuals with low BP, or in those with intensively treated arterial hypertension. 48 Low or unstable BP can subsequently result in low ocular perfusion pressure, 49 thereby increasing the risk of flow-mediated damage to RGCs. Considering that up to 40-60% of participants with DM may have concomitant hypertension, 50 51 the results of our study have important implications for the use of anti-hypertensive medications and retinal health, and highlight an area where further research is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that diabetic patients have elevated blood and serum viscosity and elevated red blood cell aggregation and adhesion, which increase the resistance to blood flow and reduce its stability in the flow process, leading to slow blood flow and decreased blood flow rate and triggering circulatory disorders ( 117 ). From a hemodynamic perspective, ocular blood flow is determined by the balance between ocular perfusion pressure and vascular resistance ( 118 ). Prolonged hyperglycemia leads to endothelial dysfunction, increased vascular resistance, abnormal retinal perfusion, and exacerbation of retinal ischemia and hypoxia ( 119 ).…”
Section: Parallelism Between Dn and Dr Developmentmentioning
confidence: 99%